(untitled) (Web of Teachers: Inderscience Research, 2024)
Intelligence plays a vital role in adapting to new learning environments by enabling individuals to process information efficiently, solve problems, and learn quickly. It supports flexibility, adaptability, and effective communication, which are essential for success in dynamic and diverse educational settings. This article examines the significance of intelligence in navigating challenges, fostering collaboration, and achieving growth in unfamiliar learning contexts. By leveraging cognitive abilities, learners can turn new environments into opportunities for personal and academic development.